Glaucocalyxin A Protects H9c2 Cells Against Hypoxia/Reoxygenation-Induced Injury Through the Activation of Akt/Nrf2/HO-1 Pathway. (9th November 2020) - Peng, Zhuo; Zhang, Rui; Pan, Longfei; Pei, Honghong; Niu, Zequn; Wang, Hai; Lv, Junhua; Dang, Xiaoyan
Myocardial infarction (MI) is one of the most serious cardiovascular diseases associated with myocardial ischemia/reperfusion (I/R) injury. Glaucocalyxin A (GLA) is a biologically active ent-kauranoid diterpenoid that has been found to ameliorate myocardial I/R injury in mice. However, the mechanism has not been fully investigated. In the present study, we aimed to investigate the effect of GLA on rat cardiomyocytes H9c2 cells exposed to hypoxia/reoxygenation (H/R). The results showed that GLA treatment improved cell viability of H/R-stimulated H9c2 cells. Administration with GLA suppressed the H/R-stimulated reactive oxygen species (ROS) production in H9c2 cells. GLA also elevated the activities of antioxidant enzymes, including superoxide dismutase and glutathione peroxidase in H/R-stimulated H9c2 cells. Moreover, GLA prevented H/R-stimulated cell apoptosis in H9c2 cells, as evidenced by increased bcl-2 expression, decreased bax expression, as well as reduced caspase-3 activity. Furthermore, GLA enhanced the activation of protein kinase B (Akt)/nuclear factor erythroid 2-related factor 2 (Nrf2)/heme oxygenase-1 (HO-1) signaling pathway in H9c2 cells exposed to H/R. Additionally, treatment with LY294002 reserved the protective effects of GLA on H/R-stimulated oxidative injury in H9c2 cells. In conclusion, these findings suggested that GLA protected H9c2 cells from H/R-stimulated oxidative damage, which was mediated by the Akt/Nrf2/HO-1 signaling pathway. Thus, GLA might be a promising therapeutic agent for the prevention and treatment of myocardial I/R.